The Durrells in Corfu: The Complete Third Season The complete third season - Goldby, Roger; Hall, Christopher, 1957-; Nye, Simon, 1958-; Hawes, Keeley, 1976-; O'Connor, Josh; Parker, Milo; Woodhouse, Callum; Waterstone, Daisy, 1994-; Georgoulis, Alexis, 1974-; Flynn, Barbara, 1948-; Savva, Anna, 1956-; Karamichos, Giorgos; et al. ([unknown]: A Sid Gentle Films LTD/Masterpiece co-production for ITV, 2018)
The beautiful island of Corfu continues to work its magic on the eccentric Durrell family. Even a visit from Aunt Hermione isn't the usual dreaded experience as the formerly formidable matriarch has embraced the laid-back Greek attitude and found romance. Leslie's also enjoying a much-improved love life with three very different girls. But there's no safety in numbers when his mother and siblings decide to interfere. Margo has (temporarily) given up on love and found a new vocation, while Gerry's obsession with animals continue to grow. As for Louisa, a trip to the UK with Larry to sort out family affairs reminds her of the restrictions of her old life. After a brush with bohemian London artists, she realizes her heart lies in her island paradise." -- container.
Originally broadcast as single episodes of a television program.
Special feature: The Durrell diaries ; favourite locations; series 2 recap ; recreating the house at Ealing Studios.
new dvd 2025 winter.
Keeley Hawes, Josh O'Connor, Milo Parker, Callum Woodhouse, Daisy Waterstone, Alexis Georgoulis, Barbara Flynn, Anna Savva, Yorgos Karamihos.
TV rating: TV-14.
DVD, wide screen (16x9); stereo.
Keywords: Durrell, Gerald, -- 1925-1995 -- Homes and haunts -- Greece -- Corfu Island -- Drama; Dorrell family -- Drama; Zoologists -- Great Britain -- Biography -- Drama; Widows -- Drama; Corfu Island (Greece) -- Description and travel -- Drama; Greece -- Drama; Television programs; Historical television programs; Fiction television programs; Television series; Video recordings for the hearing impaired; Drama; Based on the book; Drama televisions programs; Biographical television programs